The Effect of Differentiated Learning on Students’ English-Speaking Skills - Muhammad Rhomi Lazuardi; ABD Halim; Intan Karunia Putri; Wardatul Jamilah (LUNAR, 2026)
This study investigated the effect of differentiated learning on the English Speaking skills aspects of eleventh-grade students at SMAN Darussholah Singonjuruh during the 2024/2025 academic year. Using a pre-experimental one-group pre-test and post-test design, 34 students participated as respondents. Data were collected using speaking tests focusing on fluency, pronunciation, grammar, and vocabulary, and analyzed using the Wilcoxon Signed-Rank Test. The results showed a significant increase in students’ speaking scores, with the average rising from 62.21 in the pre-test to 82.94 in the post-test. The Wilcoxon test yielded a significance value of 0.000 (p < 0.05), indicating that differentiated learning had a significant positive effect on students’ speaking skills. The findings suggest that differentiated learning is an effective approach to improving students’ oral communication abilities.